An Analytical Study on the Impact of Artificial Intelligence in Enhancing Human Resource Management Practices in the IT Sector of Thiruvananthapuram District. - S.ESAKKIMUTHU,; Dr.N.RAJALINGAM, (The Bioscan, 2026)
Artificial Intelligence (AI) is increasingly redefining organizational functions particularly Human Resource Management (HRM). In the IT sector, where efficiency, innovation, and talent management are crucial, AI-based applications are transforming recruitment, training, performance appraisal, and employee engagement.